2019
DOI: 10.1038/s41433-019-0516-x
|View full text |Cite
|
Sign up to set email alerts
|

Progression and new onset of macular retinoschisis in myopic choroidal neovascularization eyes after Conbercept therapy: a post-hoc analysis

Abstract: Objectives The objective of this study is to evaluate the progression and new onset of macular retinoschisis (MRS) in the patients treated with intravitreal Conbercept injections for myopic choroidal neovascularization (mCNV). Methods Post-hoc analysis of 160 mCNV patients included in SHINY study was performed to evaluate the impact of Conbercept injection on MRS in patients with mCNV undergoing intravitreal Conbercept injections. The patients were 3:1 randomized to the study group (three loading dose and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…133,[154][155][156][157] The efficacy and safety of intravitreal anti-VEGF therapy for the treatment of myopic MNV has been evaluated in a number of large, phase III, multicenter, randomized, controlled clinical trials, including RADIANCE, 158,159 BRILLIANCE, 160 MYRROR, 161 and SHINY (Table 3). 162,163 Both the RADIANCE and BRILLIANCE studies evaluated the use of intravitreal ranibizumab 0.5 mg versus vPDT, [158][159][160] whereas MYRROR and SHINY compared the use of intravitreal aflibercept 2 mg and intravitreal conbercept 0.5 mg versus sham treatment, respectively. 161,162 Results from these randomized controlled trials have all demonstrated conclusively that intravitreal ranibizumab, aflibercept, and conbercept resulted in significant mean visual acuity gains in patients with myopic MNV at their primary end points with an excellent safety profile.…”
Section: Differential Diagnoses Differential Diagnoses Tomentioning
confidence: 99%
“…133,[154][155][156][157] The efficacy and safety of intravitreal anti-VEGF therapy for the treatment of myopic MNV has been evaluated in a number of large, phase III, multicenter, randomized, controlled clinical trials, including RADIANCE, 158,159 BRILLIANCE, 160 MYRROR, 161 and SHINY (Table 3). 162,163 Both the RADIANCE and BRILLIANCE studies evaluated the use of intravitreal ranibizumab 0.5 mg versus vPDT, [158][159][160] whereas MYRROR and SHINY compared the use of intravitreal aflibercept 2 mg and intravitreal conbercept 0.5 mg versus sham treatment, respectively. 161,162 Results from these randomized controlled trials have all demonstrated conclusively that intravitreal ranibizumab, aflibercept, and conbercept resulted in significant mean visual acuity gains in patients with myopic MNV at their primary end points with an excellent safety profile.…”
Section: Differential Diagnoses Differential Diagnoses Tomentioning
confidence: 99%
“…None of the eight eyes had progression of MRS to a FTMH or FD during the follow-up period of 12 months [ 20 ]. Zhou et al reported ten eyes had MRS progression and two eyes had new-onset MRS in 122 mCNV eyes treated with Conbercept [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal (IV) injection of anti-vascular endothelial growth factor (anti-VEGF) has been shown to effectively improve vision in patients with mCNV [ 17 , 18 ]. The progression and onset of MRS in mCNV eyes after anti-VEGF treatment have been reported [ 19 22 ], but the risk and protective factors have not yet been studied in a large series. In the present study, we collected cases of eyes with mCNV treated with anti-VEGF, investigated the clinical features, and identified the risk and protective factors for vitreoretinal interface changes after anti-VEGF treatment in highly myopic eyes.…”
Section: Introductionmentioning
confidence: 99%
“…At 9 months, conbercept‐treated eyes had further mean BCVA gain to 13.28 letters, while the sham/conbercept group gained to 11.26 letters after switching to conbercept at month 3. Post‐hoc analysis of the SHINY study assessed the development and progression of macular retinoschisis and found 10 eyes had macular retinoschisis progression with two eyes had new onset of macular retinoschisis during the study 57 . Pre‐treatment vitreoretinal adhesion was found to be associated with new onset and progression of macular retinoschisis.…”
Section: Myopic Mnvmentioning
confidence: 99%
“…Post-hoc analysis of the SHINY study assessed the development and progression of macular retinoschisis and found 10 eyes had macular retinoschisis progression with two eyes had new onset of macular retinoschisis during the study. 57 Pre-treatment vitreoretinal adhesion was found to be associated with new onset and progression of macular retinoschisis. However, the number of conbercept injections was not associated with new onset or progression of macular retinoschisis.…”
Section: Anti-vegf Therapy: Conberceptmentioning
confidence: 99%